IMPLEMENTASI KEBIJAKAN PERLINDUNGAN LAHAN PERTANIAN PANGAN BERKELANJUTAN DI KABUPATEN SIDENRENG RAPPANG (STUDI KASUS KECAMATAN MARITENGNGAE) - Husni, Muthia Fadhilah; Jabbar, Abdul; Yasin, Akhmad (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2024)
Local governments have the responsibility to manage governance and development affairs in their regions, including the agricultural sector. Regional autonomy provides freedom for local governments to regulate policies and development programs in agriculture according to the characteristics of their regions. Kabupaten Sidenreng Rappang, as a national food barn, plays a crucial role in the agricultural sector. However, data on rice production indicates a significant decline in recent years. This study identifies the implementation of policies related to the protection of agricultural land in Kabupaten Sidenreng Rappang, including the conversion of agricultural land to non-agricultural use. The research employs a qualitative method, conducting interviews to gather necessary data. There were 8 informants, including government agencies, farmer groups, and professional farmer organizations. Data analysis was performed using Nvivo 12 Plus software. The results show that sustainable agricultural land protection policies in Kabupaten Sidenreng Rappang have been implemented, as indicated by the analysis of the data showing that all four indicators of Edward III Policy Implementation Theory have been executed effectively by government agencies, farmer groups, and professional farmer organizations. Challenges faced in policy implementation include limited resources, extreme climate changes, and the level of public awareness.